Spatial Distribution of Secondary Education Services in the Western Branch of the Zliten Area (Journal of Libya for geographical studies, 2026)
This study aims to examine the spatial distribution of secondary education services in the Western Branch of the Zliten area and to identify the problems associated with this distribution by evaluating the efficiency and equity of secondary school locations. The study adopted a descriptive-analytical approach, employing statistical analysis using SPSS. Data were collected through a questionnaire administered to a sample of 200 male and female teachers distributed across secondary schools located in Al-Qasbah, Ka‘am, Al-Qazzahiyah, Al-Ghuwaylat, and Maghraghrin within the Western Branch. In addition, field studies were conducted through personal interviews with secondary school principals. The spatial distribution of schools was also analyzed using Geographic Information Systems (GIS) techniques. The study reached several findings, most notably that the distribution of secondary schools within the Western Branch is uneven. Al-Qasbah and Al-Ghuwaylat each contain three schools, while Ka‘am has only one school. In contrast, the areas of Al-Qazzahiyah and Maghraghrin lack any secondary schools, indicating an unplanned and inefficient distribution pattern. Preliminary indicators further revealed spatial disparities and insufficient school density in several neighborhoods within the Western Branch of the Zliten area. The study proposed a set of recommendations aimed at improving the spatial distribution of secondary schools in a manner that ensures equity in access to educational services and enhances the efficiency of their utilization.
Keywords: Spatial distribution; Education; Secondary education; Western Branch